Pengaruh Keterlibatan Karyawan, Keberlangsungan Financial, Biaya Operasional, Dan Digital Branding Terhadap Kinerja Umkm Padang Timur - Shintya Afiani; Riani Sukma Wijaya (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
This research is research that aims to determine: (1) the influence of employee involvement on MSME performance, (2) the influence of financial sustainability on MSME performance, (3) the influence of operational costs on MSME performance, (4) the influence of digital branding on MSME performance. The population of this research is MSMEs in Padang Timur sub-district. The number of samples used in this research was 100 respondents taken using purposive sampling techniques. The research instrument used was a questionnaire in the form of a questionnaire sheet. The analytical methods used are classical assumption testing, multiple linear regression, and hypothesis testing. The results of this research are that employee involvement has a significant effect on MSME performance, financial sustainability does not have a significant effect on MSME performance, operational costs have a significant effect on MSME performance, and digital branding has a significant effect on MSME performance.